Transcripts from the Cellular Homologs of Retroviral Oncogenes: Distribution Among Chicken Tissues - Gonda, Thomas J. (1982)
The oncogenes (v-onc genes) of rapidly transforming retroviruses have homologs (c-onc genes) in the genomes of normal cells. In this study, we characterized and quantitated transcription from four c-onc genes, c-myb, c-myc, c-erb, and c-src, in a variety of chicken cells and tissues. Electrophoretic analysis of polyadenylated RNA, followed by transfer to nitrocellulose and hybridization to cloned onc probes showed that c-myb, c-myc, and c-src each give rise to a single mature transcript, whereas c-erb gives rise to multiple transcripts (B. Vennstrom and J. M. Bishop, Cell, in press) which vary in abundance among different cells and tissues. Transcription from c-myb, c-myc, c-erb, and c-src was quantitated by a “dot-blot” hybridization assay. We found that c-myc, c-erb, and c-src transcription could be detected in nearly all cells and tissues examined, whereas c-myb transcription was detected only in some hemopoietic cells; these cells, however, belong to several different lineages. Thus, in no case was expression of a c-onc gene restricted to a single cell lineage. There appeared to be a correlation between levels of c-myb expression and hemopoietic activity of the tissues and cells examined, which suggests that c-myb may be expressed primarily in immature hemopoietic cells. An examination of c-onc RNA levels in target cells and tissues for viruses carrying the corresponding v-onc genes revealed no obvious correlation, direct or inverse, between susceptibility to transformation by a given v-onc gene and expression of the homologous c-onc gene.